Second Language Learning Research Problems and Perspectives. Papers from a Conference on Second Language Learning (Birmingham, England, February 24-26, 1984) - Centre for Information on Language Teaching and Research, London (England).; Brumfit, Christopher; Centre for Information on Language Teaching and Research, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
The principal objectives of this conference were: (1) to become aware of present research relevant to second language learning/teaching; (2) to stress the need for further research; and (3) to establish directions for this further research. Papers include: "Language Needs and Social Policy" (John Trim); "Some Priorities for Research in Second Language Learning" (Paul Meara); "An Outsider's View of Research Needs in Second Language Learning" (Robert Le Page); "Research and the Teacher of Foreign Languages in Secondary Schools" (Brian Page); "Communication Processes: What Do Second Language Learners Need to Be Able to Do?" (David Wilkins); "Language Learning and Acquisition Processes: How Can and Do People Learn?" (Steven McDonough); and "Language Learning in Education: What Research Should Be Done to Help Improve Learning?" (Rosamond Mitchell). A review and summary of the papers, a list of recent and current research in Great Britain, an extensive bibliography, and a participant list are appended. (MSE)
ERIC Note: For individual papers, see FL 016 093-099.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communicative Competence (Languages); Instructional Improvement; Language Research; Language Teachers; Learning Processes; Public Policy; Research Needs; Research Problems; Second Language Learning; Secondary Education; Collected Works, Proceedings